Analysis of distortion, corrosion and mechanical properties of welded ASTM A36 steel U-type profiles - Pereira, Josemairon Prado; Hernandez, Bruno Agostinho; Bento Gonçalves, Gilberto de Magalhães; Sousa, Edson Antonio Capello; Pereira, Jonatas Martins (International Journal of Advanced Engineering Research and Science, 2023)
Several factors affect the performance, manufacturing, and assembly of metallic profiles: equipment, welding parameters, and consumables. ASTM A36 steel profiles are widely used to obtain high-quality welded joints. Three factors in the welded joints need to remain nearly invariable and within predictable limits: distortion, corrosion, and mechanical properties. However, industries still have problems with welding steel profiles, such as warping misalignment, misfit, and poor mechanical properties. As a result, it is necessary a calibrated and affordable methodology for welding ASTM A36 steel profiles on the factory floor. Therefore, this study aims to analyse the mechanical performance of ASTM A36 steel profile welded joints using a robot welding machine. A GMAW (Metal Active Gas) welding process was applied to an ASTM A36 type U 100 x 50 profile, 3.0 mm thick, employing a Motoman UP6 robotic arm in butt joints, with and without dots. Two different rod electrode types were used (AWS ER70S-3 and ER70S-6), with a 75%Ar/25%CO2 shielding gas and current density welding set at 160.6 A and 20.5 V. A three-dimensional scanning methodology was adopted to investigate welded joint distortions. While salt spray accelerated corrosion test was used to analyse deterioration. The mechanical properties were analysed by macrography, microhardness, and chemical analyses in the Heat Affected Zone (HAZ). It was found a distortion displacement lower than 450 µm on the sample's surface, and a mass loss of 10.1 µm/year was detected in terms of corrosion resistance. There was also evidence of chemical heterogeneity between the base metal and weld, mainly in the manganese content with an average reduction of 13% in microhardness measurements when AWS ER70S-3 electrode was used. By using calibrated welding parameters and a welding robot, it was possible to obtain mechanically resistant high-quality standardised welds. This procedure can be further improved by using other profile types to implement new robotic welding procedures.